China's syndrome : Chinese military modernization and the rearming of Southeast Asia - Bitzinger, Richard A. (2009)
As China rises as a military power in the Asia-Pacific region, the countries of Southeast Asia are hedging against Chinese military adventurism by rearming themselves.